2022
DOI: 10.3390/en15197380
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Purification of Actinides Using N,O-Hybrid Donor Ligands for Closing the Nuclear Fuel Cycle

Abstract: Despite the fact that in the mass consciousness nuclear power is associated with increased environmental risks, this type of energy today remains one of the cleanest, most efficient and carbon neutral. Further development of nuclear energy is hampered by the problem of appropriate handling of spent nuclear fuel (SNF). A very attractive concept of the closed nuclear cycle has been developed to solve it. A real-life implementation of this concept requires the development of technological processes for the effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 178 publications
0
9
0
Order By: Relevance
“…The past decade has witnessed a flourishing development of actinide/lanthanide complexation and separation by employing N,O-hybrid ligands based on rigid N-heterocyclic skeletons. Shi et al reported a tetradentate N,O-hybrid ligand, N , N ′-diethyl- N , N ′-ditolyl-2,9-diamide-1,10-phenanthroline (Et-Tol-DAPhen), with well-preorganized amide oxygen and nitrogen atoms, which exhibits good extraction ability and selectivity toward actinides over lanthanides . More recently, Zabierowski et al reported that 2,2′-bipyrimidine-4,4′-dicarboxylic acid could bind to lanthanides to form stable complexes, in which the pyrimidine nitrogen atoms and carboxylic oxygen atoms involved in coordination on the same molecule always lie approximately in the same plane.…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has witnessed a flourishing development of actinide/lanthanide complexation and separation by employing N,O-hybrid ligands based on rigid N-heterocyclic skeletons. Shi et al reported a tetradentate N,O-hybrid ligand, N , N ′-diethyl- N , N ′-ditolyl-2,9-diamide-1,10-phenanthroline (Et-Tol-DAPhen), with well-preorganized amide oxygen and nitrogen atoms, which exhibits good extraction ability and selectivity toward actinides over lanthanides . More recently, Zabierowski et al reported that 2,2′-bipyrimidine-4,4′-dicarboxylic acid could bind to lanthanides to form stable complexes, in which the pyrimidine nitrogen atoms and carboxylic oxygen atoms involved in coordination on the same molecule always lie approximately in the same plane.…”
Section: Introductionmentioning
confidence: 99%
“…The extractants containing the highly preorganized phenanthroline skeleton exhibit outstanding advantages such as high extraction efficiency, fast kinetics, and strong acid resistance, which have been applied to the group separation of actinides over lanthanides from acidic solutions. The novel tetradentate ligand N , N ′-diethyl- N , N ′-ditolyl-2,9-diamide-1,10-phenanthroline (Et-Tol-DAPhen) (Figure d) reported by Xiao et al exhibited strong extraction ability toward actinides with different oxidation states ( D Th(IV) = 205, D U(VI) = 25, and D Am(III) = 6, 1 M HNO 3 ). By tailoring the substitute groups in the diamide moieties, a series of ligands were synthesized and applied to the actinide extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there is a significant interest in 1,10-phenanthroline ligands as nitrogen-containing building blocks for coordination and organometallic chemistry. , These ligands have functionalized substituents that enhance their efficiency in separating f-elements. Additionally, the presence of chiral centers in these ligands allows for asymmetric complex catalysis. Half-sandwich Ru­(II), Ir­(III), and Rh­(III) complexes with substituted 1,10-phenanthrolines have been proven to be highly effective catalysts. Furthermore, Ru­(II) complexes of substituted phenanthrolines have shown potential in treating brain cancer. , Copper­(II) and nickel­(II) complexes with asymmetric phenanthroline derivatives have also been extensively studied. Unsymmetrical 1,10-phenanthrolines have been identified as promising ligands for Ru­(II) complexes to act as photosensitizers in solar cells . Moreover, a Ru-complex of 4,7-diaminosubstituted 1,10-phenanthroline has been reported to be useful for selective dual-channel detection of Cu­(II) ions .…”
Section: Introductionmentioning
confidence: 99%